A quantitative study of teacher self-efficacy in the midst of a global pandemic - Henderson, Christie Maria (Kansas State University, 2022)
Educators have endured the difficulties of teaching during a pandemic for over eighteen months. The COVID-19 pandemic has been described as the greatest challenge for our global society since World War II (Saha and Dutta, 2020). The nuances of teaching during this experience have influenced educators to reflect on their skill set and examine their continued effectiveness in the areas of student engagement, instructional strategies and classroom management. In addition, teachers and counselors have addressed their own mental health issues and the social emotional issues of their students and families. The purpose of this study was to determine the levels of teacher self-efficacy and differences between the subgroups of veteran and novice, rural and urban, and male and female. This quantitative descriptive study examined the self-efficacy of teachers during the pandemic as measured by the Teachers Sense of Self-Efficacy Scale (Tschannen-Moran & Woolfolk Hoy, 2001). The study provided a point-in time for the lasting impact of this historical event on the self-efficacy of teachers. The results of this study indicated an overall mid-range level of self-efficacy for teachers as well as differences between select sub-groups when comparing efficacy in the areas of student engagement, classroom management and instructional strategies.
Keywords: Teacher self-efficacy; Pandemic